Dietary protein defends lean mass and maintains the metabolic benefits of glucagon receptor agonism in mice - Tatiana Lopes; David CD. Hope; Jose M. Ramos-Pittol; Anna Curtis; Jed V. Shrewsbury; Iona Davies; Zijing Zhou; Alessandro Sardini; James S. Minnion; Dirk Dormann; Gavin A. Bewick; Kevin G. Murphy; et al. (Elsevier, 2024)
Objective: Glucagon has long been proposed as a component of multi-agonist obesity therapeutics due to its ability to induce energy expenditure and cause weight loss. However, chronic glucagon-receptor agonism has been associated with a reduction in circulating amino acids and loss of lean mass. Importantly, it is currently not known whether the metabolic benefits of glucagon can be maintained under contexts that allow the defence of lean mass. Methods: We investigate the metabolic effects of the long-acting glucagon receptor agonist, G108, when administered to obese mice at low-doses, and with dietary protein supplementation. Results: Dietary protein supplementation can only fully defend lean mass at a low dose of G108 that is sub-anorectic and does not reduce fat mass. However, in this context, G108 is still highly effective at improving glucose tolerance and reducing liver fat in obese mice. Mechanistically, liver RNA-Seq analysis reveals that dietary protein supplementation defends anabolic processes in low-dose G108-treated mice, and its effects on treatment-relevant glucose and lipid pathways are preserved. Conclusion: Glucagon-mediated energy expenditure and weight loss may be mechanistically coupled to hypoaminocidemia and lean mass loss. However, our data suggest that glucagon can treat MAFLD at doses which allow full defence of lean mass given sufficient dietary protein intake. Therefore, proportionate glucagon therapy may be safe and effective in targeting hepatocytes and improving in glycaemia and liver fat.